Eksistensi Fatwa No.21/DSN-MUI/X/2001 Pada Asuransi Jiwa Syariah di PT. Prudential Life Assurance Cabang Ponorogo - Pertiwi, Linda; Abidah, Atik (Invest Journal of Sharia & Economic Law, 2021)
This article aims to review the implementation of Fatwa No. 21 / DSN-MUI / X / 2001 concerning General Guidelines for Sharia Insurance in Insurance Institutions. Sharia life insurance is a type of life insurance whose application is based on the provisions of Islam. PT. Prudential Life Assurance is a sharia life insurance company. In carrying out its activities to develop customer funds, PT. Prudential Life Assurance invests. In practice, the investment and insurance percentage determination is carried out unilaterally by the agent. Determining the percentage of this investment will affect customers' cash value claims that do not match the illustration. More specifically, in this connection, the author will analyze two aspects. First, the analysis of Fatwa No.21 / DSN-MUI / X / 2001 regarding the General Guidelines for Islamic Insurance on the implementation of the investment system at PT. Prudential Life Assurance Ponorogo Branch? Second, the analysis of Fatwa No.21 / DSN-MUI / X / 2001 regarding the General Guidelines for Islamic Insurance on the payment of cash value claims for customers at PT. Prudential Life Assurance Ponorogo Branch? The author's type of research is field research using qualitative methods, while the data collection techniques used are interviews and documentation. The analysis used uses the deductive method, namely a discussion that begins with presenting arguments, theories or provisions that are general and then put forward a specific fact. From this research, it can be concluded that the implementation of the investment system at PT. Prudential Life Assurance at the Ponorogo branch is only limited to administration. Where the agent determines the percentage of insurance and investment unilaterally to get a hefty fee, this is not following the DSN fatwa No.21 / DSN-MUI / X / 2001, which reads "investment must be made under sharia." Meanwhile, regarding the payment of cash value claims from customers that do not match the illustration, it follows the DSN fatwa No.21 / DSN-MUI / X / 2001, which reads "different claims in the amount according to the premium paid."